Optimization of a transient antibody expression platform towards high titer and efficiency. Issue 4 (25th January 2021) - Greene, Elizabeth; Cazacu, Daniela; Tamot, Ninkka; Castellano, Steven; Datar, Akshita; Kronkaitis, Anthony; Gebhard, Douglas; Reed, Jon; Mawson, Paul; Florin, Lore; Rossi, Nicholas; Lauer, Anthony; et al.
Abstract: Transient gene expression (TGE) using mammalian cells is an extensively used technology for the production of antibodies and recombinant proteins and has been widely adopted by both academic and industrial labs. Chinese Hamster Ovary (CHO) cells have become one of the major workhorses for TGE of recombinant antibodies due to their attractive features: post‐translational modifications, adaptation to high cell densities, and use of serum‐free media. In this study, we describe the optimization of parameters for TGE for antibodies from CHO cells. Through a matrix evaluation of multiple factors including inoculum, transfection conditions, amount and type of DNA used, and post‐transfection culture conditions, we arrived at an uniquely optimized process with higher titer and reduced costs and time, thus increasing the overall efficiency of early antibody material supply. We further investigated the amount of coding DNA used in TGE and the influence of kinetics and size of the transfection complex on the in vitro efficiency of the transfection. We present here the first report of an optimized TGE platform using Filler DNA in an early drug discovery setting for the screening and production of therapeutic mAbs. Abstract : CHO cells are the work horses for recombinant antibody production for biopharmaceutical industry. In this study, the authors have optimized a Transient Gene Expression (TGE) platform in CHO cells by exploring different parameters that impact TGE process including Filler DNA, DNA:TR complex ratio and incubation time, to name a few. This work provides a platform for delivery of mAbs in a discovery research setting.